2017
DOI: 10.3727/096368917x694877
|View full text |Cite
|
Sign up to set email alerts
|

Using Electrical Stimulation to Enhance the Efficacy of Cell Transplantation Therapies for Neurodegenerative Retinal Diseases: Concepts, Challenges, and Future Perspectives

Abstract: Disease or trauma-induced loss or dysfunction of neurons in any central nervous system (CNS) tissue will have a significant impact on the health of the affected patient. The retina is a multilayered tissue that originates from the neuroectoderm, much like the brain and spinal cord. While sight is not required for life, neurodegenerationrelated loss of vision not only affects the quality of life for the patient but also has societal implications in terms of health care expenditure. Thus, it is essential to deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 166 publications
(189 reference statements)
0
14
0
1
Order By: Relevance
“…In recent years, the synergy between cellular therapies and electrical stimulation has begun to be considered as a possible treatment for degenerative pathologies. This synergy addresses four main aspects: native cell survival, transplanted cell survival, transplanted cell integration, and functional synapse formation/axon regeneration (Manthey et al, 2017). While the methods of Electrical Stimulation (ES) administration are different, their influence on the preservation of retinal structure and function is similar and based on studies in animal models.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, the synergy between cellular therapies and electrical stimulation has begun to be considered as a possible treatment for degenerative pathologies. This synergy addresses four main aspects: native cell survival, transplanted cell survival, transplanted cell integration, and functional synapse formation/axon regeneration (Manthey et al, 2017). While the methods of Electrical Stimulation (ES) administration are different, their influence on the preservation of retinal structure and function is similar and based on studies in animal models.…”
Section: Discussionmentioning
confidence: 99%
“…While the methods of Electrical Stimulation (ES) administration are different, their influence on the preservation of retinal structure and function is similar and based on studies in animal models. In the rat model of retinitis pigmentosa (RP), it has been shown that ES preserved outer nuclear layer (ONL) thickness and delayed inner retinal degeneration (Manthey et al, 2017;Hanif et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The stimulation of neuronal activity might induce a more endogenous-like, and thus more physiologically relevant stimulation of NTF expression as compared to artificial supplementation. Ocular electrical stimulation (ES) has shown promising results for neuroprotective therapy in retinal and optic nerve diseases as reviewed by Sehic et al [141] and Manthey et al [142]. Here, we provide a brief overview of studies investigating ES and NTF involvement in the visual system.…”
Section: Ntfs As Neuroprotective Therapy In Glaucoma: What Informamentioning
confidence: 96%
“…BFGF is known to directly promote the survival of photoreceptors [42]. Synergy with electrical stimulation (ES) addresses four main aspects: survival of native cells, survival of transplanted cells, integration of transplanted cells, and functional formation of synapses/axon regeneration [43]. In recent years, the synergy between cell therapies and electrical stimulation has started to be considered as a possible treatment for degenerative diseases.…”
Section: Pathophysiological Co-factoriality and Cell Therapymentioning
confidence: 99%